Adequação ao selo Casa Azul da Caixa Econômica Federal de edificações do Programa Minha Casa Minha Vida - Brasileiro, Suely Benevides de Carvalho (2013)
The Construction Industry is one of the most impactful activities form de environmental point of view. The mankind lack of housing in this newmillennium is about 600 million. It is necessary to make architecture and engineering more sustainable. In Brazil, the housing program Minha Casa Minha Vida (My House, My Life) provides for the construction of about 3 million of houses. Thinking about to reduce the impacts of this program, CAIXA ECONÔMICA FEDERAL has established a certification called SELO CASA AZUL (Seal Blue House). To achieve this certification there are a number of requirements that the entrepreneur / builder must meet to have a more sustainable housing. This work shows a literature review about the actual criteria of sustainability, certification concerning sustainable building, and design decisions that can minimize the environmental impact of the constructions. The CAIXA s critéria to obtain the Seal Blue House are showed. Also a diagnostic of houses that are being built in the municipality of Paulista - PE, in this program, is presented. Two building typologies of houses were analyzed. It was found that they meet a few criteria required by the SELO CASA AZUL (Seal Blue House). Then, based on architectural design, we followed the guidelines of the CAIXAS s Guide of Environmental Sustainability and proposed changes so that it meets the criteria to pass the Seal. The results show that it is possible, even in popular constructions, to obtain the certification and contribute to sustainability.